Stratégies discursives de persuasion dans la critique de cinéma comme activité rhétorique - Topa-Bryniarska, Dominika (Studia Romanica Posnaniensia, 2017)
The present paper deals with the discursive construction of persuasiveness in media language. Based on eighty reviews of two French comedies Intouchables (2011) and Qu’est-ce qu’on a fait au Bon Dieu ? (2014), different components of the genre ‘film review’ – relatively little explored until recently – are established in the light of two operations of metonymy exploring the rhetorical argument from community. As the operations mentioned contribute to influencing the addressees’ will and decisions, they perform the phatic function linked to the rhetoric principle of movere and delectare. Accordingly, it is important to notice that the persuasive strategies reflect some methods used in advertising discourse, especially with regard to indirect means of interpretation, values and emotions, which become starting points for the deliberative dimension of the film review. These parameters permit to reduce the information verification process by applying colloquial expressions, directive speech acts, collocative pronouns and generic quantifiers, since they stem from the trustworthiness relation connected with the peripheral route of persuasive influence.